Use of music as a didactic resource for the improvement of listening in 7th grade A students of the Aurelio Prieto Muelas School - García Lagos, Silvana Marley (Machala: Universidad Técnica de Machala, 2024)
The document addresses the importance of English as a universal language and its crucial role in international communication across various fields. It emphasizes the need for a systematic approach to English teaching, involving governments, educators, students, and parents. Additionally, it identifies challenges in language education, such as a lack of resources and teacher training. The research aims to validate how integrating music into the classroom can overcome limitations like the lack of listening methodologies and the exclusive focus on grammar. Objectives include theoretically supporting the use of music, evaluating initial skills and progress, and implementing and assessing a music-based teaching system. The hypothesis is that music significantly improves students' listening skills. In conclusion, it is proposed that a balanced and well-planned English education is essential for personal and professional growth in a globalized world.
El documento aborda la importancia del inglés como lengua universal y su papel crucial en la comunicación internacional en diversas áreas. Se destaca la necesidad de un enfoque sistemático en la enseñanza del inglés, que involucre a gobiernos, docentes, estudiantes y padres. Además, se identifican los desafíos que enfrenta la enseñanza del idioma, como la falta de recursos y la capacitación docente. La investigación busca validar cómo la integración de la música en el aula puede superar limitaciones como la falta de metodologías de escucha y el enfoque exclusivo en la gramática. Los objetivos incluyen fundamentar teóricamente el uso de la música, evaluar habilidades iniciales y progresos, e implementar y evaluar un sistema de clases basado en música. La hipótesis es que la música mejora significativamente las habilidades auditivas de los estudiantes. En conclusión, se propone que una enseñanza equilibrada y bien planificada del inglés es fundamental para el crecimiento personal y profesional en un mundo globalizado.
Keywords: LISTENING; TEACHING RESOURCES; MUSIC; TEACHING SYSTEM